Strategic supplier relationships and supply chain resilience: Is digital transformation that precludes trust beneficial?. Issue 7 (27th July 2021) - Faruquee, Murtaza; Paulraj, Antony; Irawan, Chandra Ade
Abstract : Purpose: The purpose of this study is to investigate the role that communication, trust and digital transformation can play in the relationship between joint problem-solving and supply chain resilience. More specifically, the authors try to examine the possibility of digital transformation as a replacement for trust within a joint problem-solving context. Design/methodology/approach: A survey instrument was developed and administrated to manufacturing firms within the United Kingdom and the United States. Based on data collected from 291 senior managers, multiple linear regressions were conducted through a customized process model to test the proposed hypotheses. Findings: The results point to the actual impact of digital transformation being far more complicated than the initial benefits that it appears to bring within a supply chain. Thus, technology is only effective when applied within the right context. The authors showcase that the trio of digital transformation, trust and joint problem-solving can be highly valuable to establish supply chain resilience and that further investigation on the interrelationships between these concepts is warranted. Practical implications: Manufacturing firms that aim to adopt new technologies should not consider advanced digital technologies as an alternative to trust. While digital transformation can improve resource sharing and integration, governance mechanisms–such as trust–will remain the cornerstones of strategic supplier relationships. Therefore, supply chain partners must strive to achieve a balance between trust and the right type of digital technology. Originality/value: This study contributes to the growing literature focusing on the role that digital transformation can play in developing supply chain capabilities. It adds an early empirical insight on the role of technology and governance in joint problem-solving and supply chain resilience.